SERAT YUSUF: SASTRA ISLAM POPULER DI JAWA TIMUR - Pudjiastuti, Titik; Buduroh, Mamlahatun; Mu’jizah, Mu’jizah; Suharjo, Rias; Setyani, Turita Indah; Rahmawanto, Dwi (Paradigma: Jurnal Kajian Budaya, 2025)
Serat Yusup is one of the popular Islamic literary works in Java, especially in East Java. This literary work is a handwritten ancient manuscript written in the form of tembang macapat, in Javanese language, and using Pegon or Javanese script. Serat Yusup which create by the students (santri) is inspired by Surah Yusuf, the 12th Surah of the Quran. As a literary work, its story differs significantly from its inspirational text, and there are so many of it. In relation to this, the question arises: what are the reasons behind the creation of Serat Yusup and why is it highly favored by the Muslim community in East Java? This article aims to uncover the popularity of Serat Yusup in East Java. The primary data source for this article is ancient manuscripts; therefore, the appropriate method to study it is philology. From the discussion of its content, it is estimated that there are three reasons for the adaptation of Serat Yusup: it represents Islamic teachings, Javanese culture, and human ideals. In conclusion, Serat Yusup was composed in the form of Javanese Islamic literary work not only for aesthetic fulfilment and creative expression of its student creators but also to spread Islam in East Java.